Estimates of the national wealth of Denmark 1845-2013 - Kim Abildgren (Danmarks Nationalbank, 2015)
In Denmark, there is a long-standing tradition for estimating the stock of national wealth. However, the most recent estimate is from 1985 and the longest time series available covers only the period 1950-1978. In this paper, we review the earlier estimates and present new annual time series estimates on the stock of national wealth in Denmark 1845-2013 based on a broad range of contemporary and historical statistics as well as results from previous academic research. The coverage of our national wealth is broadly in line with the most recent international national-accounts guidelines. As robustness checks, we compare this new data set with recent time-series estimates on the long-term development in the national wealth in other European countries and earlier estimates of the national wealth in Denmark. We find that the wealth-toincome ratio in Denmark has followed a U-shaped pattern over the long run, which corresponds to developments in other European countries and indications from earlier estimates of the national wealth of Denmark. However, in two areas the historical development in Denmark differ from that of other European countries. First, there were no sharp declines in the Danish wealth-to-income ratio around the two world wars as was the case in France and Germany due to war-related destruction of the capital stock. Secondly, the wealth-to-income ratio in Denmark declined significantly from 1870 to 1913 whereas the ratios were basically stationary in France and UK during the same period. This reflects a faster growth in population and real gross domestic product per capita in Denmark during this period, which saw the first wave of industrialisation in Denmark.
Keywords: E01; N33; N34; 330; National wealth; Economic history